ANALISIS KRITIS TERHADAP PERAN DAN EFEKTIVITAS PROLEGNAS DALAM PEMBENTUKAN KEBIJAKAN HUKUM DI INDONESIA: SEBUAH PENDEKATAN TEORITIS DAN PRAKTIS - Makruf, Solihan; Rusmana, Dian; Rosidin, Utang (Gapenas Publisher, 2024)
This research critically assesses the role and effectiveness of the National Legislation Programme (Prolegnas) in the process of legal policy-making in Indonesia. This research aims to assess the extent to which Prolegnas can plan legislation in accordance with national legal needs. The method used is a literature review, in which various legal sources and reports on the implementation of Prolegnas are analysed in depth. The results of this study will provide insight into the various obstacles and challenges faced in the implementation of Prolegnas. It is also expected that this research will provide recommendations on how to improve the effectiveness of Prolegnas in supporting a more targeted and sustainable legal policy